2012
DOI: 10.1002/jbm.b.32735
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on the tribocorrosion behavior of CpTi in the oral environment: synergistic interactions of wear and corrosion

Abstract: Despite reports of CpTi being electrochemically stable down to pH 2.0, this study suggests degradation peaks at near neutral pH values in the presence of motion. At pH 6.0, the passive film layer, typically protecting the surface of titanium may not be reformed cohesively, resulting in more tribocorrosion products at the surface, which are easily sheared off. These findings elevate concern with regard to dental implants because the average pH of the oral cavity is 6.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 48 publications
4
87
1
10
Order By: Relevance
“…After sliding, average R S , R P , and CPE are calculated to be 269.1 ± 6.9 X, 1.2 ± 0.11 9 10 7 X, and 2.6 ± 0.4 9 10 -5 Fs , respectively. These values are similar to those reported in literature [43,44]. However, Mathew et al reported R P values to be much lower [43].…”
Section: Electrochemical Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…After sliding, average R S , R P , and CPE are calculated to be 269.1 ± 6.9 X, 1.2 ± 0.11 9 10 7 X, and 2.6 ± 0.4 9 10 -5 Fs , respectively. These values are similar to those reported in literature [43,44]. However, Mathew et al reported R P values to be much lower [43].…”
Section: Electrochemical Analysissupporting
confidence: 91%
“…These values are similar to those reported in literature [43,44]. However, Mathew et al reported R P values to be much lower [43]. Figure 5a shows a corrosion-only PD curve of a Ti-V sample in Artificial Saliva (AS) of pH = 6.5, and Fig.…”
Section: Electrochemical Analysissupporting
confidence: 88%
See 3 more Smart Citations